Mutant huntingtin affects endocytosis in striatal cells by altering the binding of AP-2 to membranes - Borgonovo, Janina Edith (2013)
Clathrin-mediated endocytosis plays an important role in the maintenance of neuronal integrity in the synaptic terminals. Here we studied the effect of anomalous polyglutamine expansion in huntingtin on the interaction of coat proteins with membranes, in areas of mouse brain or in cultured striatal cells. We observed that this anomaly induces a redistribution of AP-2, but not other coat proteins, from the membrane to the cytosol in the striatum, and in the cultured striatal cells. It was also noted that huntingtin associates with AP-2, and that this association decreases due to the mutation in huntingtin. This decreased receptor-mediated endocytosis, measured by the internalization of transferrin in the mutated cells. It was also confirmed that huntingtin mutation made the cells more vulnerable to the action of quinolinic acid, with an increasing degradation of the AP-2 alpha subunits. On the basis of these results, we conclude that abnormal polyglutamine expansion in huntingtin affects clathrin-mediated endocytosis, and may be one of the pathogenic mechanisms of neurodegeneration.